2013
DOI: 10.1152/ajpendo.00349.2013
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of heart lipoprotein lipase-knockout mice confirms a role for triglyceride in optimal heart metabolism and function

Abstract: IJ.Rescue of heart lipoprotein lipase-knockout mice confirms a role for triglyceride in optimal heart metabolism and function. Am J Physiol Endocrinol Metab 305: E1339 -E1347, 2013. First published October 1, 2013; doi:10.1152/ajpendo.00349.2013.-Hearts utilize fatty acids as a primary source of energy. The sources of those lipids include free fatty acids and lipoprotein triglycerides. Deletion of the primary triglyceride-hydrolyzing enzyme lipoprotein lipase (LPL) leads to cardiac dysfunction. Whether heart L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This could explain the increase in cardiac fatty acid levels seen in our studies with SGLT2 inhibition. Others have shown that ANGPTL4 overexpression in cardiomyocytes leads to reduced LpL activity and small hearts that are prone to failure 23 ; cardiac LpL deficiency shows a similar increase in afterload induced heart failure 47 . We postulate that reduced heart expression of ANGPTL4 improves heart energy production, which in turn will improve heart function.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the increase in cardiac fatty acid levels seen in our studies with SGLT2 inhibition. Others have shown that ANGPTL4 overexpression in cardiomyocytes leads to reduced LpL activity and small hearts that are prone to failure 23 ; cardiac LpL deficiency shows a similar increase in afterload induced heart failure 47 . We postulate that reduced heart expression of ANGPTL4 improves heart energy production, which in turn will improve heart function.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitate Uptake into the Heart In Vivo In vivo palmitic acid uptake was measured as previously described with modifications (Khan et al, 2013). Palmitic acid [9, 10-3 H(N)]-5 mCi (PerkinElmer, NET043005MC) was complexed with 6% BSA at 37 C. Male GSK-3a S21A KI and control mice were fasted for 2 h and were intravenously administered the labeled BSA-conjugated palmitic acid and 400 mM of unlabeled BSA-conjugated palmitic acid via the femoral vein with 10 6 counts and euthanized 5 min post-injection.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…The elevation of cardiac triglyceride level and reduction of cardiac FFA may be explained by the marked reduction of LPL expression, indicating the impaired triglycerides clearance. Loss of LPL-derived lipids leads to decreased triglyceride lipolysis and increased glucose uptake in heart, resulting in cardiac dysfunction ( Augustus et al, 2003 , 2006 ; Khan et al, 2013 ). Although neither BM-MSCs nor iPSC-MSCs treatment could alter the serum FFA level, treatment with iPSC-MSCs restored cardiac FFA level, in support of the reversal of cardiac CD36 expression after treatment with iPSC-MSCs, which accounts for over 50% FA uptake in the heart.…”
Section: Discussionmentioning
confidence: 99%